Study of climate change effects on rain height for satellite microwave links - Yong, Xin Yu (2024)
In this research paper, the study of climate change effects on rain height for satellite microwave links in Malaysia is being conducted. Rain height is one of the important variables in determining the effective slant path for signal transmission of satellite communication systems. When the height of the rainfall increases, the length of the slant path increases which causes the signal being attenuated by the raindrops increase. Since the rain height is widely depends on the global surface temperature, the issues of climate change might cause effects on the rain height. Data being used in this research are obtained from NCEP/NCAR reanalysis database which including the reanalysis data for altitude and temperature. Furthermore, the ITU-R recommendation method such as ITU-R P.839 and ITU-R P.618 recommendation model had been adopted in obtaining the rain height values as well as the rain attenuation values respectively. Then, a simple AI predictive model for rain height is being developed by using Artificial Neural Network (ANN) algorithms with Python programming language. The rain height value is found to have a positive correlation with the global temperatures and both of them have a significant increase throughout the past 30 years in Malaysia. This rain attenuation also proved to have an increasing trend. Lastly, an AI predictive model with Artificial Neural Network (ANN) algorithms that have the good performance and acceptable accuracy in predicting the future rain height values had been developed. This can provide accurate data for future design work of satellite-based communication systems.